2022
DOI: 10.1186/s40538-021-00280-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pyrene-induced changes in root activity on growth of Chinese cabbage (Brassica campestris L.), and the health risks caused by pyrene in Chinese cabbage at different growth stages

Abstract: Background Polycyclic aromatic hydrocarbons (PAHs) pose a potential risk to ecological safety and human health. They have a range of effects on plant growth and there have been few reports on the health risks associated with ingestion of vegetable crops at different growth stages. Methodology In this study, a pot experiment in which Chinese cabbage (Brassica campestris L.) were grown in a greenhouse for 75 days was used to investigate the dose–effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Agoun-Bahar et al ( 2018) emphasized that the presence of naphthalene strongly affected the reduction in root growth when in direct contact with pollutants. Yang et al (2022) reported that a high concentration of pyrene as aromatic hydrocarbon reduced growth parameters and root and shoot biomasses of beans by 60% in contaminated soil compared to those of the control treatment.…”
Section: Stem and Root Weightsmentioning
confidence: 99%
“…Agoun-Bahar et al ( 2018) emphasized that the presence of naphthalene strongly affected the reduction in root growth when in direct contact with pollutants. Yang et al (2022) reported that a high concentration of pyrene as aromatic hydrocarbon reduced growth parameters and root and shoot biomasses of beans by 60% in contaminated soil compared to those of the control treatment.…”
Section: Stem and Root Weightsmentioning
confidence: 99%